Climate variability and cultural eutrophication at Walden Pond (Massachusetts, USA) during the last 1800 years - Stager, J. Curt; Wiltse, Brendan; Hubeny, J. Bradford; Yankowsky, Eric; Nardelli, David; Primack, Richard (PLOS ONE, 2018)
Recent shifts in the ecological condition of Walden Pond, MA, are of potentially wide interest due to the lake's importance as a cultural, historical, and recreational resource in addition to its scientific value as an indicator of local and global environmental change. Algal microfossils in six sediment cores document changes in hydroclimate and trophic status of the lake during the last 1800 years and extend two previous sediment core records of shorter length. Low percentages of planktonic diatoms in the longest cores (WAL-3, WAL-15) indicate shallowing and/or greater water clarity associated with a relatively arid interval during the Medieval Climate Anomaly, ca. A.D. 1150-1300, Cultural eutrophication of the lake since the A.D. 1920s caused diatoms in the genera Asterionella and Synedra to increase in relative abundance at the expense of Cyclotella, Discostella, and the chrysophyte alga Mallomonas allorgel. Percentages of Asterionella and Synedra have remained fairly stable since A.D. 2000 when a previous sediment core study was conducted, but scaled chrysophytes have become more numerous. These findings suggest that, although mitigation efforts have curtailed anthropogenic nutrient inputs to Walden Pond, the lake has not returned to the pre-impact condition described by Henry David Thoreau and may become increasingly vulnerable to further changes in water quality in a warmer and possibly wetter future.
Keywords: BOREAL LAKES; canada; CRAWFORD LAKE; DEPTH MODELS; ENVIRONMENTAL-CHANGE; ice-age; new-england; NORTH-AMERICA; NORTHEASTERN UNITED-STATES; organic-matter